Molecular Epidemiology of Methicillin-Resistant Staphylococcus aureus - Bo Shopsin; Barry N. Kreiswirth (Emerging Infectious Diseases, 2001)
Subtyping methicillin-resistant Staphylococcus aureus (MRSA) isolates and tracking nosocomial infections have evolved from phenotypic to genotypic approaches; most laboratories now depend on pulsed-field gel electrophoresis (PFGE). We discuss the limitations of current image-based genotyping methods, including PFGE, and the advantages (including ease of entering data into a database) of using DNA sequence analysis to control MRSA infections in health-care facilities.